CoBr2-catalyzed straightforward synthesis of quinoxalines via dehydrogenative coupling strategy - Dubey, Shivansh; Punji, Benudhar (Chemistry-an Asian Journal, 2025)
Establishing a benign and straightforward protocol for synthesizing biorelevant and synthetically valuable quinoxaline is very important. Herein, we report a simple and efficient protocol for the sustainable synthesis of diverse quinoxaline derivatives catalyzed by cobalt salt. The reaction proceeds through the dehydrogenative coupling of alkyl and aryl ethane 1,2-diols with aryl diamines in the presence of a catalytic CoBr2/K2CO3. The usage of the greener solvent 2-MeTHF and the release of H2 and H2O as the sole byproducts make the process advantageous. The protocol led to the synthesis of diverse quinoxalines bearing synthetically useful functionalities, such as fluoro, chloro, bromo, cyano, trifluoromethyl, and ether. The reaction is presumed to proceed via the dehydrogenative-condensation pathway involving a cobalt-hydride intermediate.
Keywords: cobalt; dehydrogenative coupling; heterocycles; ligand-free process; Quinoxaline

syn-Selective hydrosilylation and hydroboration of alkynes at room temperature catalyzed by a phosphine-free (NNN)Fe(ii) complex - Pradhan, Chandini; Dubey, Shivansh; Samal, Pragnya Paramita; Krishnamurty, Sailaja; Punji, Benudhar (Catalysis Science & Technology, 2025)
Catalytic hydrofunctionalization of alkynes is the ideal and atom-economical route to synthesize vinylsilanes and vinylboronates, which are valuable organic building blocks. However, the process suffers from using expensive phosphine-ligated catalysts, sensitive organometallic activators, and elevated reaction temperatures. To overcome these challenges, herein, we developed a series of phosphine-free (NNN)-ligated iron complexes and demonstrated their potential as efficient catalysts for the hydrosilylation and hydroboration of both internal and terminal alkynes using NaOtBu as an activator. The reactions proceeded smoothly using 1.5 mol% catalyst loading at room temperature and provided syn-selective vinylsilanes and vinylboronates. This hydrofunctionalization exclusively delivered mono-silylated and mono-borylated vinyls with tolerance of sensitive functionalities. At the same time, terminal alkynes provided excellent anti-Markovnikov selectivity with thermodynamically feasible beta-(E)-vinylsilanes and beta-(E)-vinylboronates. The presence of an N-H moiety in the ligand backbone is crucial in generating an Fe(ii) active catalyst and facilitating the catalytic process. Mechanistic investigations, including controlled reactions and external additive experiments, were performed to propose a redox-neutral reaction mechanism with iron maintaining its +2 oxidation state throughout the cycle. The DFT energy calculations unanimously support the proposed reaction mechanism.